Antimicrobial activity of herbal extracts on Staphylococcus aureus and Propionibacterium acnes - P. Leelapornpisid (2018)
Excoecaria cochinchinensis Lour, Salvia officinalis Lour and Argyreia nervosa (Burm.f) Bojer, leaves were extracted by various extracting procedures, using different solvents for testing the antimicrobial activities against Staphylococcus aureus (ATCC 25923) and Propionibacterium acnes isolated from patients. We obtained 13 extracts. Using well diffusion method, ethanolic and water extracts of E. cochinchinensis and S. officinalis were found to be effective against these organisms whereas all extracts of A. nervosa were inactive. The chemical anti-acne agents such as azelaic acid, benzoyl peroxide and commercial clindamycin phosphate were also included in the experiment. The minimum inhibitory concentration (MIC) for the active extracts was examined by broth dilution method. The results showed that the MIC of water extracts from E. cochinchinensis and S. officinalis were 1.56 and 3.13 mg/ml for S. aureus (ATCC 25923), 1.56 and 6.25 mg/ml for P. acnes, respectively. The minimal bactericidal concentration (MBC) were 3.13 and 6.25 mg/ml for S. aureus (ATCC 25923), 6.25 and 12.5 mg/ml for P. acnes, respectively. These results were comparable with azelaic acid, better than benzoyl peroxide but not as good as clindamycin phosphate. Furthermore, the water extract from E. cochinchinensis exhibited outstanding effective activities against clindamycin resistant S. aureus (P31 and Fl14) isolated from patients. The MIC and MBC were 0.78 and 3.13 mg/ml, respectively. The phytochemical preliminary study on ethanolic and water extracts of E. cochinchinensis was also performed for screening chemical constituents. Tannin and phenolic compounds were found. From the thin layer chromatographic pattern compared to standard tannic acid and gallic acid, the water extract revealed the same Rfvalue (0.75) as gallic acid. The purpose of this study was to find preliminary data for the development of anti-acne products from natural plant extracts. © ISHS 2005.